Attitudes towards ICT integration into curriculum and usage among university lecturers in Vietnam. - Hue, Ly Thanh; Ab. Jalil, Habibah (International Journal of Instruction, 2013)
Although the integration of information and communication technologies (ICT) into the curriculum was a crucial process in ensuring the quality of education, it has still not been given greater concern by the administrators and lecturers in some universities in Vietnam. The purpose of this descriptive-survey research is to determine lecturers' attitudes towards ICT integration into the curriculum and its use in the classroom. The research questions sought to measure the frequency of ICT use in teaching and learning among lecturers and their attitudes towards ICT integration into the curriculum to improve teaching; and to determine if a correlation existed between lecturers' attitudes towards ICT integration into the curriculum and their ICT use in the classroom. A population of 109 lecturers at a public university in Vietnam participated in this survey. The results of the correlation analysis identified a slightly moderate positive relationship between lecturers' attitudes towards ICT integration into the curriculum and their ICT use in the classroom. Although ICT was not highly used, lecturers recognized the benefits of ICT that they had chosen to incorporate into their teaching. These findings could be used for future research to promote positive educational changes through the integration of ICT into the curriculum in universities.